Consanguineous marriage, prepregnancy maternal characteristics and stillbirth risk: a population‐based case–control study. (7th July 2015) - Maghsoudlou, Siavash; Cnattingius, Sven; Aarabi, Mohsen; Montgomery, Scott M.; Semnani, Shahriar; Stephansson, Olof; Wikström, Anna‐Karin; Bahmanyar, Shahram
Abstract: Introduction: Consanguineous marriage is associated with increased risks for congenital anomalies, low birthweight, and other adverse perinatal outcomes. In this population‐based, case–control study we investigated the association between consanguineous marriage (first‐cousin marriage) and stillbirth risk, using prospectively collected information from prepregnancy visits. Material and methods: From 2007 to 2009, we identified 283 stillbirths (cases) and 2088 randomly selected live control births through prepregnancy visits in rural Golestan, Iran. The associations between consanguinity and prepregnancy maternal characteristics and stillbirth risk were examined using multivariate logistic regression. Results: The rate of consanguineous marriage was 19.4% among cases and 13.6% among controls. Consanguinity was associated with increased stillbirth risk [odds ratio (OR) 1.53; 95% CI 1.10–2.14]. The association was significantly increased for preterm stillbirth (< 37 gestational weeks) (OR 2.43; 95% CI 1.46–4.04) but not for term stillbirth (≥ 37 weeks) (OR 1.14; 95% CI 0.75–1.74). Low and high maternal age, underweight, obesity, nulliparity, a history of infertility or miscarriage, previous obstetric complications (preeclampsia, preterm delivery, and stillbirth in previous pregnancies) were also associated with increased stillbirth risks. Conclusions: Consanguineous marriage is associated with increased risk of stillbirth, particularly preterm stillbirth. Findings for other maternal risk factors for stillbirth in rural Iran are consistent with previously reported findings from high‐income countries.